THE ROLE OF NATIONAL CULTURAL CENTERS IN ENSURING INTERNATIONAL SOLIDARITY AND HARMONY IN UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
In this article, national in the process of inter-ethnic relations in Uzbekistaninformation about the importance of cultural centers, the role of state policy in the formation of national harmony, the processes of inter-ethnic tolerance in Uzbekistan.